Cultural Values In The Film 'Najih' By Pondok Pesantren Dalwa Charles Sanders Peirce's Semiotic Analysis - Hartono, Alfina; Rohanda, Rohanda; Fauziah, Isma (Jurnal Studi Agama, 2024)
This research aims to describe the cultural values contained in the film "Najih" by Pondok Pesantren Dalwa. The film Najih tells the story of a young man who is determined and never gives up in his journey to learn Arabic. This research is a qualitative descriptive study that uses the research object in the form of the film "Najih" by Pondok Pesantren Dalwa. This research focuses on the film "Najih" with objects in the form of stills from different scenes in the film. Researchers classify signs based on representation, object and interpreter. Through the analysis applied, a lot of data was found that revealed the cultural values in the film "Najih". These cultural values include elements such as knowledge, belief, art, morality, law, customs, skills and habits. This can be seen from the data presented in the research.